Solvent-dehydrated cadaveric dermis: a new allograft for pubovaginal sling surgery - Onur, R; Singla, A (Blackwell Publishing, 2005)
Aim. The aim of this study was to evaluate the efficacy of solvent-dehydrated cadaveric dermis in pubovaginal sling surgery for the first time in the literature. Methods. Twenty-five women with stress urinary incontinence underwent pubovaginal sling surgery using 2 x 12 cm allograft dermis. Preoperatively, all patients were evaluated by a detailed urogynecologic evaluation, voiding diary, pelvic examination and urodynamic investigation. Outcome was assessed by the Urogenital Distress Inventory short form and standardized follow-up questionnaires. Results. Twenty (80%) patients were cured of stress incontinence symptoms. Seventeen wore no pad and three reported occasional stress urinary incontinence and used no or one pad at a mean follow up of 12 months. Five (20%) patients in our series experienced the same amount of leakage as before the surgery. Seventy-six percent of the patients indicated that urinary incontinence was no longer negatively affecting their daily life and were satisfied with the procedure. Conclusions. Questionnaire-based assessment of outcome suggests that solvent-dehydrated cadaveric dermis is effective in the treatment of stress urinary incontinence. However, larger and comparative prospective studies with long-term results and randomized comparison of tissue preparation techniques are warranted.
Keywords: allograft dermis; stress; sling; tissue processing; urinary incontinence